Assessing the Effectiveness of the Enforcement and Implementation of the Ban on Importation of Some Selected Second-Hand Items - Gohoho, Emmanuel Sena; Ewedji, Christabel (Advances in Social Sciences Research Journal, 2024)
Importation of second hand items has been a concern in Ghana. In 1994, Ghana passed the Legislative Instrument (LI) 1586, which outlawed the importation; clearance and sale of used undergarments because they were found to be unhygienic and presented a health hazard. Two decades after the introduction of the ban of second items, these items can still be found on the Ghanaian markets. The Ghanaian market continue to be flooded with these second hand items despite the existing ban on their importation into the country. The study investigated the effectiveness of the banned items. Data was collected from both traders and custom officials using simple random and purposive sampling methods respectively. The study found that the implementation of the ban on the selcted items is not effective. Customs is complicit in the countinuous importation of the banned items into the country. Some Customs officials have allowed the trade to continue to fester by conniving with traders. This has created an enabling environment for traders to continually import the banned items into the country. The study recommends that Customs Division of GRA should launch an investigation into their operations and identify the officials engaged in these activities and the necessary actions be applied.